2002
DOI: 10.1023/a:1021250813367
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Few studies have been conducted in the area of social stories, and the limitations of these studies (i.e., improper story construction and methodological confounds) raise questions about effectiveness of social story interventions. This study examined the effectiveness of properly constructed social stories that have been introduced into the natural environment to target the disruptive behavior of three children with autism. A multiple baseline design across participants was employed, and a decrease in disrupt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(27 citation statements)
references
References 1 publication
1
26
0
Order By: Relevance
“…In addition, the findings of this study reinforced the findings of Scattone et al (2002) who found that social stories which were developed effectively and introduced in the natural environment in autistic children had proven a decrease in disruptive behavior after implementing the intervention on all the subjects of the study. This finding also explains that the problem of disruptive behaviors was beyond the subconscious of the students themselves.…”
Section: Discussion and Implications Of The Studysupporting
confidence: 84%
“…In addition, the findings of this study reinforced the findings of Scattone et al (2002) who found that social stories which were developed effectively and introduced in the natural environment in autistic children had proven a decrease in disruptive behavior after implementing the intervention on all the subjects of the study. This finding also explains that the problem of disruptive behaviors was beyond the subconscious of the students themselves.…”
Section: Discussion and Implications Of The Studysupporting
confidence: 84%
“…19 – 22 Social stories must meet specific guidelines for format and language. 18 , 23 When created according to these specifications, social stories decrease tantrums and inappropriate behaviors and increase positive behaviors such as initiating social interactions and responding on task. 23 …”
Section: Creation Of An Eye Examination Protocolmentioning
confidence: 99%
“…These stories are carefully designed to be within the comprehension level of the child and can be used with younger and older children accordingly (66). Although Social Stories are widely accepted due to the connection to prevailing theories of autism, evidence-based research is needed.…”
Section: Behavioral Intervention Modelsmentioning
confidence: 99%